An interactive multimedia courseware for primary school student to learning english language - Wong, Wei Jie (2023)
With the development of science and technology, internet-based learning has become one of the emerging and most common learning methods in recent years. Interactive multimedia courseware is one of the critical terms in order access to high-quality educational environment. The reason is multimedia have brought out improvement in the learning and teaching process. Nowadays, English as a global language and the most common language that people use to communicate. It led to more parents’ great importance placed on the English language education for their children. The proposed of this paper is to develop an interactive multimedia course for children to learn English. This system consists of a learning module, practice module and quiz module that is suitable for children whose ages range between 7 to 9. Through this system, the ultimate goal is able to improve the proficiency level of children.